Effects of integrative neuromuscular training intervention on physical performance in elite female table tennis players: A randomized controlled trial - Xiong, J.; Li, S.; Cao, A.; Qian, L.; Peng, B.; Xiao, D. (PLOS ONE, 2022)
Objectives: To investigate the effects of integrative neuromuscular training (INT) on physical performance in elite female table tennis players. Methods: Twenty-four Chinese elite female table tennis players were randomized into either INT (n = 12) group or control group (CON; n = 12). INT group performed four INT sessions every week for 8 weeks, while CON group performed traditional physical fitness training. One repetition maximal (1RM), vertical jump, Y balance test and 30-meter sprinting performance were tested before and after intervention. Results: No between groups differences were detected for any tests before intervention. Significant group by time (before or after intervention) interaction effects were observed in 1RM, vertical jump, bilateral lower limb reaching distance at posteromedial and posterolateral directions, and right leg at the anterior direction for the Y balance test (all p < 0.05), but not for the left leg at the anterior direction or the 30-meter sprinting performance (both p > 0.05). Post-hoc analysis for measurements with significant interactions revealed that all significant changes were at the ING group (all p < 0.05), while no changes for the CON group were observed (all p > 0.05). Conclusion: Eight weeks INT significantly improved strength, power and balance in Chinese elite female table tennis players. Adopting INT in table tennis players may improve their physical performance and lead to better sports performance